Forecasting costs in the accommodation and catering services sector under the risk and uncertainty - Vitalija Jarmolkovič; Algita Miečinskienė (Mokslas: Lietuvos Ateitis, 2022)
The article examines cost forecasting in the accommodation and catering services sector under the risk and uncertainty. It is emphasized that cost management is significant for increasing a company’s profits or surviving in the face of market difficulties. This article aims to forecast the costs of sales in the accommodation and catering services sector under the risk and uncertainty. when the types of costs that have an essential impact on the cost of sales were determined. The first part of the article analyzes the distribution of costs, their management directions and theoretical aspects of the impact of risk and uncertainty on costs. The second part of the article is devoted to the development of the research methodology. The third part of the article presents empirical research on identifying the costs that have the most significant impact on the cost of sales and forecasting the total costs under the risk and uncertainty in the accommodation and catering services sector.